A32 POPULATION-BASED ESTIMATE OF HEPATITIS C VIRUS PREVALENCE IN ONTARIO, CANADA. (1st March 2018) - Bolotin, S; Feld, J; Garber, G; Wong, W W; Guerra, F; Mazzulli, T
Abstract: Background: Hepatitis C virus (HCV) is the most burdensome infectious illness in Canada. Current screening strategies miss a significant proportion of cases, leaving many undiagnosed. Elevated HCV prevalence in the baby-boomer cohort has prompted calls for birth-cohort screening in this group. However, Canada lacks population-level data to support this recommendation. Aims: The aim of this study was to obtain a population-based estimate of the prevalence of HCV infection in Ontario residents born between 1945 and 1974, estimate of the number of HCV cases by age cohort in Canada, and generate evidence to underpin policy recommendations on birth-cohort screening. Methods: We tested anonymized residual sera in five-year age-sex bands, weighted according to the population across Ontario, for anti-HCV antibody, and tested all antibody positive and 10% of negative sera for HCV RNA. We performed descriptive epidemiological analysis and used a logistic regression model to determine HCV risk-factors. Results: Of 10, 006 sera analyzed, 155 (1.55%, confidence interval (CI) 1.31, 1.79) were positive for HCV antibody. For males, who comprised 107/155 (69.03%) of positive samples, the highest prevalence was 3.00% (95% CI 1.95, 4.39), for those born between 1960 – 1964. For females, the highest prevalence was 1.56% (95% CI 0.83, 2.65), for those born between 1955 – 1959. Both male sex and year-band of birth were significantly associated with positive HCV serostatus. Eighty of 145 (55.2%) antibody positive sera were also RNA positive, and 17/993 (1.7%) antibody negative sera were RNA positive. Using a previously published cost-effectiveness model, our analysis showed that a birth-cohort screening program for Ontario would be cost-effective. Conclusions: HCV prevalence in Ontario is highest among those in baby-boomer birth cohort, and higher than previous estimates. Given the development of highly effective, curative therapy, birth cohort screening should be strongly considered, particularly for those born between 1950 – 1969. Funding Agencies: Public Health Ontario Project Initiation Fund